Perspektif Mahasiswa Jurusan Bisnis Terhadap Penggunaan Aplikasi Digital Banking Dalam Pembayaran UKT Di Politeknik Negeri Balikpapan - Made Lia Ananda Dewi; Ferdy Novri (Pusat Riset dan Inovasi Nasional, 2025)
This study explores the perceptions of Business Department students at Politeknik Negeri Balikpapan regarding the use of digital banking applications for paying the Single Tuition Fee (UKT). Employing a qualitative approach, primary data was collected through in-depth interviews with selected respondents. Digital banking is designed to streamline financial transactions in line with technological advancements and the growing digitalization of Indonesia's banking sector. As part of the younger generation immersed in an increasingly digital environment, students are viewed as a key demographic expected to adopt and utilize digital banking systems not only for tuition payments but also for managing.